Noninferiority trial in veal calves on the efficacy of oxytetracycline and florfenicol treatment for pneumonia guided by quick thoracic ultrasound - Stan Jourquin; Florian Debruyne; Laurens Chantillon; Thomas Lowie; Randy Boone; Jade Bokma; Bart Pardon (Journal of Dairy Science)
ABSTRACT: Purchase dependent calf rearing systems, such as the white veal industry, systematically rely on antimicrobial mass medication (metaphylaxis) to counter respiratory tract infections. Despite mounting criticism, the industry fears that without metaphylaxis, mortality would drastically increase. This randomized clinical trial aimed to compare the efficacy of a quick thoracic ultrasonography (qTUS) individualized treatment length between oxytetracycline (OTC) and florfenicol (FF). Regression of maximum consolidation depth <1 cm was used as a criterion for cure and to stop antimicrobial treatment. Additionally, the study assessed the associations of consolidation depth at treatment initiation with cure and treatment duration. The trial involved 320 veal calves, randomly assigned into one of 2 groups: one receiving OTC (n = 160) and the other FF (n = 160) on d 1 (2-d metaphylaxis). Clinical scoring and qTUS were done on d 1 and every 48 h for a 10-d period. After d 1, only calves with consolidations ≥1cm were given further treatment. On each time point, maximum consolidation depth was used to categorize calves into 4 qTUS categories: healthy (no consolidation), mild pneumonia (consolidation <1 cm), moderate pneumonia (consolidation 1–3 cm) and severe pneumonia (consolidation ≥3 cm). Cure, treatment duration and the number of antimicrobial dosages (NAD) were compared between treatment groups. In addition, pathogen identification and antimicrobial susceptibility testing was performed on isolates from nonendoscopic broncho-alveolar lavage fluid. On d 1, 30.0% (96/320) of the calves had consolidation ≥1cm, which increased to 50.9% (162/318) by d 9. After single metaphylactic treatment, cure was 20.9% (9/43) and 20.9% (9/43) in the OTC and FF group, respectively. Calves with severe pneumonia had lower odds to be cured after first treatment than calves with moderate pneumonia (odds ratio = 0.17; 95% CI: 0.04–0.63). By d 9, final cure of the initial cases was 27.9% in both the OTC and FF groups. In both groups, cure was similar at all observation points. Overall, final cure of all calves with either moderate or severe pneumonia during the trial was 41.2% (52/102) and 19.0% (12/63), respectively. Median (Med) treatment duration was 4 d (interquartile range [IQR] = 2–6; minimum [Min] = 2; maximum [Max] = 8) and was similar in both treatment groups. Treatment duration for calves with moderate pneumonia (Med = 6; IQR = 4–6; Min = 2; Max = 8) was lower than the median treatment duration of calves with severe pneumonia (Med = 8; IQR = 4–8; Min = 2; Max = 8). When compared with calves with mild pneumonia on d 1, calves with moderate and severe pneumonia had significantly longer treatment durations. In this study, cure was low and not different between both antimicrobials. Categorizing calves based on consolidation depth appears useful as both cure and treatment duration were different for the mild, moderate, and severe groups.